Beliefs: Quality Teaching Practicum Vs Quality Teachers - Gui Chan Choo; Md Melor Yunus; MOHAMED AMIN EMBI (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2019)
Teaching practicum is one of the important aspects in teacher education programme as it concerns preparation of quality teachers and it embraces all the learning experiences of pre-service teachers in schools. Teaching practicum is a real challenge for the pre-service teachers because their performance during teaching practicum will foreshadow the future success of the pre-service teachers. Therefore, the aim of this paper is to investigate Teaching English as a Second Language (TESL) pre-service teachers’ beliefs about teaching practicum and identify what components of teacher education programme that contribute pre-service teachers’ views about teaching practicum. Data was collected via a questionnaire survey of third year TESL undergraduates from University of Malaya. The data was analyzed using descriptive statistics. The findings will be presented and elaborated upon in this paper. For further understanding, this paper also discusses the pre-service teachers’ beliefs according to the two main aspects namely, (i) importance of teaching practicum and (ii) confidence and uncertainty about teaching practicum.